Experimental study of the influence of stitched nylon threads in glass-fiber-reinforced polymer two-dimensional multilayer composite on tensile strength - Lira Martínez, Manuel Alejandro; Gaona Tiburcio, Citlalli; Almeraya Calderón, Facundo; Jáquez Muñoz, Jesús Manuel; Zalapa Garibay, Manuela Alejandra (Multidisciplinary Digital Publishing Institute, 2023)
Stitched filaments are known to modify the mechanical properties of glass-fiber-reinforced polymers 2D (GFRPs 2D), so studying the effect on mechanical properties is underway to determine the critical variables involved. This research focuses on the study of the tensile strength effect of stitched low-density Barkley FBA BGQS15-15 nylon monofilament on biaxial E-Glass Saertex 830 g/m2 (+/−45◦) cured with Polyester Sypol Resin 8086 CCP using a vacuum infusion process. Four specimens were made with longitudinal distances between the stitched reinforcements of 0.5, 1.0, 1.5, and 2.0 cm, respectively. Tensile strength tests based on standard ASTM D3039 were performed to study how stitching can affect toughness, Young’s modulus, deformation, ultimate strength, and yield strength. The results indicated that the stitching increases Young’s modulus up to 99.2%, UTS is increased by up to +3.14%, deformation decreases by up to −41.66%, and toughness decreases by up to −36.89%. Although the stitching’s main function is to increase interlaminar resistance, it also induces the formation of stress concentrations by the new threads, and premature failure in the matrix was shown.